Psychometric Properties of the Persian Version of the Evaluation of Ankylosing Spondylitis Quality of Life (EASi‐QoL) and Ankylosing Spondylitis Disease Activity Score (ASDAS) Questionnaires: A Cross‐Sectional Study - Maryam Hosseini; Amirmasoud Kazemzadeh Houjaghan; Ghazal Behzad; Sahar Ghorbanpour; Seyede Zahra Emami Razavi; Mohaddeseh Azadvari; Shafieh Movaseghi; Negar Salaminour (Health Science Reports)
ABSTRACT Background and Aims Ankylosing spondylitis (AS) is a chronic inflammatory disease that affects quality of life (QoL) due to its impact on physical and emotional well‐being. Accurate and reliable tools are needed to assess disease activity and QoL in different cultural contexts. This study aimed to evaluate the psychometric properties of the Persian versions of the Evaluation of Ankylosing Spondylitis Quality of Life (EASi‐QoL) and Ankylosing Spondylitis Disease Activity Score (ASDAS) scales in Iranian AS patients. Methods A cross‐sectional study was conducted on 70 AS patients referred to a tertiary hospital in Tehran. Patients completed the EASi‐QoL, and 39 also completed the ASDAS questionnaire. The translation followed the forward–backward method. Reliability was assessed using Cronbach's α for internal consistency and intraclass correlation coefficient (ICC) for test–retest reliability. Content validity was evaluated using the content validity ratio (CVR) and Content Validity Index (CVI). Test–retest reliability was examined using Spearman's rank correlation for non‐normally distributed data. Results The ICC values for EASi‐QoL ranged from 0.71 to 0.82, while Spearman's correlation coefficients ranged from 0.63 to 0.80. For ASDAS, all items except Question 1 had ICC and Spearman's correlation coefficients above 0.8, indicating high test–retest reliability. The average CVR for EASi‐QoL was 0.56, and for ASDAS it was 0.68. The CVI for relevance, clarity, and simplicity ranged from 0.86 to 0.96 for both scales, confirming good content validity. Conclusion The Persian versions of the EASi‐QoL and ASDAS scales demonstrate adequate reliability and validity. These tools are suitable for assessing QoL and disease activity in Iranian AS patients, providing culturally relevant measurements for clinical and research settings.